Efektivitas Model Pembelajaran Concept Attainment untuk Meningkatkan Hasil Belajar pada Mata Kuliah Studi Keislaman di PAI Unipdu Jombang - Arifin Aina'ul Mardliyah; M. Yahya Ashari Ali Muhsin (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2019)
This study aims to describe the effectiveness of learning Islamic Studies oriented Concept Learning Learning Model in terms of several aspects as follows: 1) The activities of students while participating in learning Islamic Studies oriented Learning Concept Concept Attainment Model; 2) Students' responses to Islamic learning activities oriented to Concept Attainment Learning Model Learning; 3) Learning Outcomes of students towards learning activities oriented Islamic Studies Learning Model Concept Attainment; 4) Barriers or constraints faced during the learning process of Islamic Studies oriented at Concept Learning Model attainment. In this study, subjects were taken from students of 6th Semester PAI Unipdu Jombang. The researcher is a lecturer in Islamic Studies in PAI 6th Semester class interested in conducting research especially in the class because of the heterogeneity of the class and it appears from the attitudes of students in learning quite diverse. Data collection is done by means of tests and interviews. Furthermore, to test the credibility of the data, time triangulation is performed. At different times tests are given and interviews with problems are equivalent to previous tests. Therefore, the authors conducted research to determine the learning outcomes of students in using the Concept Attainment Learning Model. This research uses "one group pretest-posttest design". Data were collected using tests, and analyzed with descriptive statistical analysis.